The determinants of regional migration in Great Britain: a duration approach - Martyn J. Andrews; Ken Clark; William Whittaker (Institute for the Study of Labor (IZA), 2008)
Using data from the first fourteen waves of the British Household Panel Survey, we estimate a discrete duration model of interregional migration in Great Britain. By exploiting retrospective information on residency we control for late entry as well as unobserved heterogeneity. We find considerable duration dependence in region of residence in the raw data, most but not all of which disappears when controlling for observable and unobservable differences between individuals. Older workers are less likely to switch region while the better educated are more mobile. There are also some differences between males and females in their likelihood to migrate.
urn:nbn:de:101:1-20081126429
Keywords: C14; 330; Migration; duration; hazard; panel data; regional labour markets; Regionale Arbeitsmobilität; Binnenwanderung; Statistische Bestandsanalyse; Großbritannien